Effect of TMS laterality on clinical outcomes in treatment resistant depression patients with comorbid anxiety - a retrospective study - Caussat, Thomas; Blair, Brian; Oberman, Lindsay M. (Frontiers in Psychiatry, 2025)
ObjectivesHigh-frequency repetitive transcranial magnetic stimulation (rTMS) of the left-hemisphere dorsolateral prefrontal cortex (DLPFC) is FDA cleared for the treatment of adult treatment-resistant major depressive disorder (MDD). Though off-label, sequential bilateral stimulation (SBS), which combines high-frequency left-hemisphere and low-frequency right-hemisphere DLPFC stimulation, is offered in various clinics to treat depression with comorbid anxiety. Few systematic studies investigate the comparative efficacy of the SBS protocol versus the FDA-label protocol for the clinical management of depression with comorbid anxiety. The objective of the current study was to compare the efficacy of HF-LUS to that of SBS within a clinical setting where both are offered to patients with anxious depression. Based on both theories of the pathophysiology of anxious depression as well as clinical practice, we hypothesized that SBS would result in greater symptom reduction as compared to HF-LUS.MethodsThis open label, retrospective cohort study included 86 patients with MDD and comorbid anxiety who received either high frequency left unilateral stimulation (HF-LUS) (n=44) or SBS (n=42). Patient Health Questionnaire 9 (PHQ9), General Anxiety Disorder 7 (GAD7) questionnaire, a self-reported depression (SRD) Likert scale, and a self-reported anxiety (SRA) Likert scale were used to quantify changes in depressive and anxiety symptoms.ResultsInconsistent with our hypothesis, both groups saw a significant improvement in depression and anxiety symptoms with no difference in course nor degree of improvement. Improvements in depression and anxiety were significantly positively correlated in both bilateral and unilateral cohorts.ConclusionsBilateral rTMS may not provide any additional therapeutic advantages over the standard FDA-cleared left unilateral rTMS protocol for anxious depressive patients.